Improved Super‐Resolution Microscopy with Oxazine Fluorophores in Heavy Water1. Issue 34 (4th July 2013) - Lee, Steven F.; Vérolet, Quentin; Fürstenberg, Alexandre
<x xml:space="preserve">Abstract</x> Brighter dyes in heavy water: A simple and cost‐effective method increases the brightness of a whole class of commonly used red‐emitting fluorophores, including ATTO655, ATTO680, and ATTO700. Replacing water (H2O) by heavy water (D2O) in the imaging buffer doubles the fluorescence quantum yield of these dyes and significantly improves the localization precision in super‐resolution imaging.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>